External oxide layers formed by the oxidation procedure in FeMnSi and FeMnSiCr shape memory alloys and their effects - Tatar, Cengiz; Kok, Mediha; Kanca, M. Sait; Tatar, Beyhan (Iop Publishing Ltd, 2024)
Shape memory alloys are exposed to high temperatures to improve their properties and functionality. Through this process, oxidation inevitably occurs due to the presence of oxygen in the environment, which interacts with the alloying elements. Oxidation adversely affects the hardness of alloys, leading to a decline in their overall quality. In this study, the oxidation behavior parameters of FeMnSi and FeMnSi-Cr alloys and the oxide layers formed during this process were investigated in Fe-based alloys with high usage potential. Both non-isothermal and isothermal oxidation processes were applied to alloys and the oxidation parameters were determined. Subsequently, the changes in the crystal structure, microstructure, and magnetic properties of the alloys subjected to isothermal oxidation at 400-500-600-700-800 degrees C were investigated. It was found that the oxidation behavior of both alloys intensified with rising oxidation temperatures, as evidenced by crystal structure and microstructural analyses, which indicated deeper penetration into the alloys at elevated temperatures. Furthermore, an increase in magnetization values was noted alongside the oxidation process. A comparison of the oxidation characteristics between FeMnSi and FeMnSi-Cr alloys revealed that the oxidation parameters for the chromium doped FeMnSi alloy were comparatively lower.
Keywords: FeMnSi based alloys; shape memory material; oxidation; magnetic property